Perceived fairness of direct-to-consumer genetic testing business models - Philipp A. Toussaint; Scott Thiebes; Manuel Schmidt-Kraepelin; Ali Sunyaev (Electronic Markets, 2022)
Although consumers and experts often express concerns regarding the questionable business practices of direct-to-consumer (DTC) genetic testing services (e.g., reselling of consumers' genetic data), the DTC genetic testing market keeps expanding rapidly. We employ retail fairness as our theoretical lens to address this seeming paradox and conduct a discrete choice experiment with 16 attributes to better understand consumers' fairness perceptions of DTC genetic testing business models. Our results suggest that, while consumers perceive privacy-preserving DTC genetic testing services fairer, price is the main driver for fairness perception. We contribute to research on consumer perceptions of DTC genetic testing by investigating consumer preferences of DTC genetic testing business models and respective attributes. Further, this research contributes to knowledge about disruptive business models in healthcare and retail fairness by contextualizing the concept of retail fairness in the DTC genetic testing market. We also demonstrate how to utilize discrete choice experiments to elicit perceived fairness.
Keywords: D12; D22; D49; I11; 620; Direct-to-consumer genetic testing; Business models; Retail fairness; Genetic privacy; Discrete choice experiment